Native American adolescent narrative written stories of stress. Issue 1 (13th January 2019) - Lowe, John R.; Kelley, Melessa N.; Hong, OiSaeng
Abstract: Objective(s): The purpose of this paper is to report study findings related to themes of stress and coping strategies experienced by non‐reservation‐based Native American adolescents as expressed by their written stories. Design: A qualitative descriptive narrative approach was used to capture written stories of stress. Analysis: Key concepts and themes were identified by using the consensual qualitative research (CQR) approach from the participant's stories of stress. Results: Written stories of stress were collected and analyzed from a convenience sample of 179 Native American adolescent's ages 13–18‐years old. Five major themes related to experiences of stress emerged from the stories including (a) relationships, (b) responsibilities, (c) socioeconomic status, (d) negative coping strategies, and (e) positive coping through Native‐Reliance. Conclusion: The findings reveal the importance of understanding the types and response to stress experienced by Native American adolescents.